2021
DOI: 10.1002/ajmg.a.62571
|View full text |Cite
|
Sign up to set email alerts
|

Extending the phenotype of DeSanto‐Shinawi syndrome: A case report and literature review

Abstract: DeSanto-Shinawi syndrome (DESSH, OMIM #616708) is a rare autosomal dominant neurodevelopmental disorder caused by loss-of-function variants in the WAC gene. Affected individuals are characterized by neonatal hypotonia, developmental delay, intellectual disability, behavioral problems, and dysmorphism. Epilepsy is present in some of the patients with DESSH. By far, less than 30 affected individuals have been reported worldwide. Herein, we report a 9-year-old Chinese girl with molecularly substantiated DESSH wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 16 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Future studies should evaluate the functional impact of the variants as it is still unclear whether the different phenotypes represent different diseases or a continuum of one disorder due to allelic combinations and allelic severity at the locus. 13 Our report provides novel LSS variants to be added to the list of APMR4 and highlights the clinical heterogeneity of LSS-related disorders. Moreover, we suggest that some neuroimaging clues can be relevant for an early diagnosis.…”
Section: Romano Et Al Described a Number Of Cases From Different Ethnic-mentioning
confidence: 88%
See 4 more Smart Citations
“…Future studies should evaluate the functional impact of the variants as it is still unclear whether the different phenotypes represent different diseases or a continuum of one disorder due to allelic combinations and allelic severity at the locus. 13 Our report provides novel LSS variants to be added to the list of APMR4 and highlights the clinical heterogeneity of LSS-related disorders. Moreover, we suggest that some neuroimaging clues can be relevant for an early diagnosis.…”
Section: Romano Et Al Described a Number Of Cases From Different Ethnic-mentioning
confidence: 88%
“…13,15,16 The p.(Ile342Ser) variant was found to significantly reduce LSS protein expression and completely abolish its enzymatic activity resulting in no lanosterol production. 13,15 The p. phenotype-genotype correlation, we found that the map positions of the individual pathogenic variant alleles were not related to the observed clinical disease. However, cases with a more severe phenotype were more likely to have a biallelic combination of a LoF allele plus a missense.…”
Section: Romano Et Al Described a Number Of Cases From Different Ethnic-mentioning
confidence: 99%
See 3 more Smart Citations